The Typological Classification of the Hebrew of Genesis: Subject-Verb or Verb-Subject? - Robert D. Holmstedt (Journal of Hebrew Scriptures, 2011)
, the Object can precede or follow both the Subject and the Verb, and adverbs and prepositional phrases can be thrown into a variety of positions. To the reader word order often seems to be random, but grammarians have long agreed that it is not random or ‘free’. Describing precisely what determines the order of words, though, remains an elusive task. Yet, it is universally understood that determining a rhyme and reason for the variation exhibited in the biblical texts would provide access to subtle linguistic cues the ancient authors used to get their message across. And so many Hebraists have attempted to identify the patterns. As with all investigations, though, the initial assumptions strongly influence the conclusions and for Hebrew word order studies the almost universal starting point has been to assume a basic Verb-Subject order. In this essay I challenge this assumption, thereby potentially undercutting the methodologies and conclusions of the vast majority of existing word order studies. I introduce, describe, and illustrate the typological linguistic criteria for determining basic word order and conclude, contrary to near-consensus position, that Biblical Hebrew is better classified as a Subject-Verb language.